PHOTOMETRIC INVESTIGATION OF DR AND - Vasilyeva, S. V.; Mkrtichian, D. E. (Одеські астрономічні публікації, 2017)
. Based upon photographic observations obtained with a 48-cm reflector AZT-S OAO, 236 estimates of the unique RR lyr - type star DR And have been derived. 6 moments of maximum light are listed, these being represented fairly enough by GCVS (1985) elements. The 3-rd order trigonometric polynomial fit corresponds to the period P =0d.56318 ±0 d. 00001 (clos to the GCVS value), initial epoch HJD Max=2445121.466±0d..003, Max=12m.06 ±0 m.04, Min=13 m.14 ±0 m.06. Light curve variations may be attributed to the Blazhko effect.